The Impact of Earnings Management on Value- Relevance of Financial Statement Information - V. Mojtahedzadeh; S. Sadeghi Askari (مطالعات تجربی حسابداری مالی, 2010)
This study examines the impact of earnings management on the value -relevance of financial statement information by considering short-term and long-term discretionary accruals. This study uses valuation framework, developed by Ohlson (1995) and Jones (1991) as basis for developing two distinct models to examine short-term and long-term discretionary accruals.10 hypotheses have been designed for this purpose. To examine these hypotheses we use the information of 100 companies listed on Tehran - Stock -Exchange during 1383–1387 and Pierson correlation. The results demonstrate that, both Earnings and Book Value have value-relevance information about firms' value. Moreover, earnings management via short-term, long- term  and  total  discretionary  accruals  reduce  value  relevance  of earnings but value relevance of book value reduce only in presence of earnings management via long-term discretionary accruals.